Adipose-Derived Mesenchymal Stem Cells Enhance Ovarian Cancer Growth and Metastasis by Increasing Thymosin Beta 4X-Linked Expression - Yijing Chu; Min You; Jingjing Zhang; Guoqiang Gao; Rendong Han; Wenqiang Luo; Tingting Liu; Jianxin Zuo; Fuling Wang (Stem Cells International)
As shown in our previous studies, growth and metastasis of ovarian cancer can be regulated by adipose-derived mesenchymal stem cells (ADSCs). However, the underlying mechanism has not yet been revealed. In this study, a proteomics analysis was performed to compare protein expression treated with and without ADSCs in ovarian cancer cells. Protein levels were altered in ovarian cancer cells due to the treatment of ADSCs. Thymosin beta 4 X-linked (TMSB4X) levels changed dramatically, and this protein was identified as one of the most important candidate molecules contributing to the tumour-promoting effects of ADSCs. Compared with the cells that are cultured in the normal growth medium, the TMSB4X levels cultured in ADSC-conditioned medium increased significantly in ovarian cancer cells. Furthermore, the growth and invasion of cancer cells were decreased, even in the ADSC-conditioned medium treatment group (P<0.05), by the inhibition of TMSB4X. As shown in the bioluminescence images captured in vivo, increased ovarian cancer’s growth and metastasis, along with elevated TMSB4X expression, were observed in the group of ADSC-conditioned medium, and the tumour-promoting effect of ADSCs was attenuated by the inhibition of TMSB4X. Based on our findings, increased TMSB4X expression may play a role in accelerating the ADSC-mediated proliferation, invasion, and migration of ovarian cancers.